Forest degradation, changing workforce structure and population redistribution: the case of Birhors in Jharkhand - Firdos, Sohel (2005)
This paper attempts to capture the trajectory of change in the livelihood patterns of the Birhors, one of the smallest tribal groups of central India, in the context of the massive degradation of forest resources and its impact on the population growth of the tribe in Jharkhand. The destruction of forest cover has ruined the Birhors' traditional livelihood occupation of rope making and the pursuit of alternative activities such as agriculture has been beset with problems. Contrary to the commonly held view, the Birhor population has not been diminishing; rather they are getting redistributed as a result of the dismantling of their traditional economic activity. - Reproduced.
Keywords: Forests - India - Jharkhand; Forests